Intestinal Parasites, Anemia and Nutritional Status in Young Children from Transitioning Western Amazon - Marques, Rejane C. (Int J Environ Res Public Health, 2020)
Young children are particularly vulnerable to the chronic sequelae of anemia, including poor nutritional status. The aim of this study was to assess intestinal parasitic-infections and nutritional status (anemia and linear growth) in preschool children living in contemporary Amazonian communities. A cross-sectional study measured children’s intestinal parasites and hair-Hg (HHg)—biomarkers of fish consumption, hemoglobin levels, and growth (anthropometric Z-scores). Children came from traditional-living families (Itapuã), and tin-mining settlements (Bom Futuro) representing current transitioning populations. It covered 937 pre-school children (from 1 to 59 months of age) from traditional (247) and immigrant tin-mining families (688). There was a high prevalence of intestinal polyparasitic-infection in children from both communities, but mild anemia (hemoglobin concentrations) and moderate (chronic) malnutrition were more frequent in children from traditional families than in children from tin-mining settlers. Children from traditional families ate significantly more fish (HHg mean of 4.3 µg/g) than children from tin-mining families (HHg mean of 2.3 µg/g). Among traditional villagers, children showed a significant correlation (r = 0.2318; p = 0.0005) between hemoglobin concentrations and HHg concentrations. High rates of parasitic infection underlie the poverty and attendant health issues of young children in the Brazilian Amazon. The intestinal parasite burden affecting poor Amazonian children resulting from unsafe water, lack of sanitation and poor hygiene is the most urgent environmental health issue.